2020
DOI: 10.1177/0025802419896935
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the persistence of laundered semen stains on fabric using a forensic light source system, prostate-specific antigen Semiquant test and DNA recovery-profiling

Abstract: Semen stains on the clothes of victims of sexual assault can remain as evidence even after garments have been laundered. In this study, we aimed to investigate the effectiveness of commonly preferred methods to detect semen stains in two different fabric types that were laundered with different washing machine programmes and washing powders, and to obtain a DNA profile from the semen stains. For this purpose, a comprehensive study was performed on semen-stained underwear using three different methods for stain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Karadayı et al. 17 and Morris et al. 25 achieved better DNA recovery from semen-stained clothes that they kept for one month and eight months, respectively, than did Farmen et al., 26 who stored the clothes for only one day.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Karadayı et al. 17 and Morris et al. 25 achieved better DNA recovery from semen-stained clothes that they kept for one month and eight months, respectively, than did Farmen et al., 26 who stored the clothes for only one day.…”
Section: Discussionmentioning
confidence: 97%
“…In two different studies previously conducted by Karadayı et al. 17 and Morris et al., 25 the effects of biological and non-biological detergents on seminal stained fabrics were investigated. These two studies showed that non-biological detergents are relatively less effective at removing semen stains on cotton fabrics than biological detergents are.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many terrorism and natural disasters have caused ISSN : 1411 3724 Eksakta : Berkala Ilmiah Bidang MIPA many fatalities, some of which can no longer be recognized or identified due to damage to some or all parts of the victim's body. To be able to identify victims, genetic information is needed (DNA (deoxyrebous nucleid acid) from the victim [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%